Assessment of cardiac function in children with congenital adrenal hyperplasia: a case control study in Cameroon - J . Tony Nengom; S. Sap Ngo Um; D. Chelo; R. Mbono Betoko; J. Boombhi; F. Mouafo Tambo; A. Chiabi; S. Kingue; P. Koki Ndombo (BMC, 2017)
Abstract Background High level of androgens found in congenital adrenal hyperplasia (CAH) seems to have a deleterious effect on heart function. We therefore evaluate cardiac function of children with CAH in comparison with a healthy group. Methods We carried out a case-control study in the single endocrinology unit of the Mother and Child Center of Chantal Biya's Foundation. Cases were matched for age and genotypic sex to 2 healthy controls. We analyzed the ejection fraction (LVEF), fractional shortening and left ventricular mass; output and cardiac index; E and A waves velocities, E/A ratio and the mitral deceleration time and diameter of the left atrium; tricuspid annular plane systolic excursion and pulmonary artery systolic pressure were also measured. Results We included 19 patients with a median age of 6.26 ± 3.75 years and 38 controls stackable distribution. The left ventricular mass of cases was greater than that of controls. A case of reversible cardiomyopathy on hormone replacement therapy was found. For the cases, the average ejection fraction was 71.95 ± 7.88%; the average fractional shortening was 40.67 ± 7.02%. All these values ​​were higher than those of controls, although the difference was not statistically significant. Diastolic left ventricular function was more impaired among the cases. Right ventricular function was similar in both groups. These abnormalities were highly correlated to the late age at diagnosis and duration of treatment. Conclusion This study shows an altered cardiac function in CAH compared to healthy control and highlights importance of an early diagnosis of cases, a tight control of androgens levels and a regular monitoring of cardiac function.